A Public Health Strategy for the Opioid Crisis. (November 2018) - Saloner, Brendan; McGinty, Emma E.; Beletsky, Leo; Bluthenthal, Ricky; Beyrer, Chris; Botticelli, Michael; Sherman, Susan G.
Drug overdose is now the leading cause of injury death in the United States. Most overdose fatalities involve opioids, which include prescription medication, heroin, and illicit fentanyl. Current data reveal that the overdose crisis affects all demographic groups and that overdose rates are now rising most rapidly among African Americans. We provide a public health perspective that can be used to mobilize a comprehensive local, state, and national response to the opioid crisis. We argue that framing the crisis from a public health perspective requires considering the interaction of multiple determinants, including structural factors (eg, poverty and racism), the inadequate management of pain, and poor access to addiction treatment and harm-reduction services (eg, syringe services). We propose a novel ecological framework for harmful opioid use that provides multiple recommendations to improve public health and clinical practice, including improved data collection to guide resource allocation, steps to increase safer prescribing, stigma-reduction campaigns, increased spending on harm reduction and treatment, criminal justice policy reform, and regulatory changes related to controlled substances. Focusing on these opportunities provides the greatest chance of making a measured and sustained impact on overdose and related harms.